A Perspective on the Stereodefined N,O-Acetals: Synthesis and Potential Applications - Kim, Haejin; Rhee, Young Ho (Synlett, 2012)
Developing chemical reactions that rapidly introduce molecular diversity in a controlled manner represents a prime goal in synthetic organic chemistry. In this regard, our recent studies on the asymmetric synthesis and utilization of stereodefined N,O-acetal opens up a conceptually new methodology. The synthesis of labile N,O-acetals was accomplished by highly efficient and chemoselective Pd-catalyzed asymmetric hydroamination of alkoxyallenes. Furthermore, the utility of the stereodefined N,O-acetals as a stereodiversity-generating element was established by the gold-catalyzed cycloisomerization. In addition to these results, new aspects of the N,O-acetals as diversity-generating elements are also discussed.
Keywords: hydroamination; allenes; N,O-acetal; piperidines; diversity